(untitled) (Strathmore Law Review, 2020)
On 30 November 1999, the Heads of State of the East African Community met in Arusha, Tanzania, and concluded the Treaty for the establishment of the East African Community. The Treaty came into force on 7 July 2000. The founding members of this Community were Kenya, Uganda, and Tanzania. Rwanda and Burundi acceded to the Treaty in 2007 while South Sudan acceded to the Treaty in 2016. While the treaty has the potential of promoting unity among the partner states, this is threatened by the fact that it fails to address how Partner States should implement it. A critical analysis of the jurisprudence from the East African Court of Justice and those of the Court of Justice of the European Union shows that community law is an autonomous legal order in which Partner States have accepted to cede part of their sovereignty to the community. Therefore, community law, unlike international law which houses it, has primacy over the municipal law of the Partner States, notwithstanding their constitutional philosophies. This paper seeks to examine how East African Community Law is implemented by partner states by reviewing the EAC Treaty, the decisions of the East African Court of Justice and the municipal laws of partner states. Decisions of the Court of Justice of the European Union on the implementation of European Union Law by Partner States of the European Union are discussed as lessons to be learnt in the East African Community.